2015
DOI: 10.6001/biologija.v61i1.3106
|View full text |Cite
|
Sign up to set email alerts
|

Acute cold stress and mild hypothermia impact on short-term, working memory and attention

Abstract: The effect of single acute cold water exposure on the cognitive function (short-term, working memory and attention) was examined in 25 male subjects who were exposed to 14 °C cold water (air temperature ~22 °C, rh ~45%) in the semi-recumbent posture (up to the shoulders) until the rectal temperature (T<sub>re</sub>) dropped to 35.5 °C. 6 subjects were excluded from the study, because we do not reach a necessary condition to drop their (T<sub>re</sub>) to 35.5 °C in 170 minutes during a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 56 publications
2
6
0
Order By: Relevance
“…The heat-induced reduction in CBF is mediated primarily by arterial hypocapnia secondary to heat-induced hyperventilation; this observation is evidenced by a partial (Brothers et al 2009) or full (Nelson et al 2011;Bain et al 2013) restoration of CBF during heat stress when eucapnia is acutely restored or when hyperventilation is voluntarily supressed (Tsuji et al 2015(Tsuji et al , 2019. Functionally, each of these stressors in isolation -hypoxia, cold, and heat -have been shown to impair cognitive function (Simmons et al 2008;Muller et al 2012;Paulauskas et al 2015;Piil et al 2017). The link between CBF and CDO 2 to cognitive functioning is complex in these environments.…”
Section: Introductionmentioning
confidence: 99%
“…The heat-induced reduction in CBF is mediated primarily by arterial hypocapnia secondary to heat-induced hyperventilation; this observation is evidenced by a partial (Brothers et al 2009) or full (Nelson et al 2011;Bain et al 2013) restoration of CBF during heat stress when eucapnia is acutely restored or when hyperventilation is voluntarily supressed (Tsuji et al 2015(Tsuji et al , 2019. Functionally, each of these stressors in isolation -hypoxia, cold, and heat -have been shown to impair cognitive function (Simmons et al 2008;Muller et al 2012;Paulauskas et al 2015;Piil et al 2017). The link between CBF and CDO 2 to cognitive functioning is complex in these environments.…”
Section: Introductionmentioning
confidence: 99%
“…We have shown that a stressful event can induce the release of many stress hormones and neuromodulators ( 2 ). In recent years, studies have shown that exposure of humans to acute stressors influences cognitive processing and performance [e.g., ( 3 5 )]. Acute stress used in these studies refers to participants' psychobiological response to a brief laboratory stress induction paradigm, such as cold water pressure [also called cold pressor stress (CPS); e.g., ( 6 )], the Trier Social Stress Test [TSST; ( 7 )], short film clips [e.g., ( 8 , 9 )], and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Up until now, some researchers have focused specifically on the effects of acute stress on human WM and the available data are equivocal. Literature shows that human WM performance after acute stress can be impaired ( 5 , 9 14 ), as well as improved, not affected, or both improved and impaired ( 3 , 6 , 8 , 15 20 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations